Epigenetic silencing of miR-137 is an early event in colorectal carcinogenesis - Balaguer, Francesc; Link, Alexander; Lozano, Juan Jose; Cuatrecasas, Miriam; Nagasaka, Takeshi; Boland, C. Richard; Goel, Ajay (Cancer Research, 2010)
Global downregulation of microRNAs (miRNA) is a common feature in colorectal cancer (CRC). Whereas CpG island hypermethylation constitutes a mechanism for miRNA silencing, this field largely remains unexplored. Herein, we describe the epigenetic regulation of miR-137 and its contribution to colorectal carcinogenesis. We determined the methylation status of miR-137 CpG island in a panel of six CRC cell lines and 409 colorectal tissues [21 normal colonic mucosa from healthy individuals (N-N), 160 primary CRC tissues and their corresponding normal mucosa (N-C), and 68 adenomas]. TaqMan reverse transcription-PCR and in situ hybridization were used to analyze miR-137 expression. In vitro functional analysis of miR-137 was performed. Gene targets of miR-137 were identified using a combination of bioinformatic and transcriptomic approaches. We experimentally validated the miRNA:mRNA interactions. Methylation of the miR-137 CpG island was a cancer-specific event and was frequently observed in CRC cell lines (100%), adenomas (82.3%), and CRC (81.4%), but not in N-C (14.4%; P < 0.0001 for CRC) and N-N (4.7%; P < 0.0001 for CRC). Expression of miR-137 was restricted to the colonocytes in normal mucosa and inversely correlated with the level of methylation. Transfection of miR-137 precursor in CRC cells significantly inhibited cell proliferation. Gene expression profiling after miR-137 transfection discovered novel potential mRNA targets. We validated the interaction between miR-137 and LSD-1. Our data indicate that miR-137 acts as a tumor suppressor in the colon and is frequently silenced by promoter hypermethylation. Methylation silencing of miR-137 in colorectal adenomas suggests it to be an early event, which has prognostic and therapeutic implications. ©2010 AACR.
CRIS-Team Scopus Importer:2025-10-13